Actor-network theory and technology innovation : advancements and new concepts - Tatnall, Arthur (Hershey, PA : Information Science Reference, 2011)
'This book provides a comprehensive look at the development of actor-network theory itself, as well as case studies of its use to assist in the explanation of various socio-technical phenomena'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Diffusion of innovations; Technological innovations -- Social aspects; Actor-network theory